Investigation of the structural and acoustic properties of biodegradable nonwovens from chicken feathers that are environmental waste - Kocatepe, Sureyya; Erol, Muslum; Pasayev, Nazim (Indian Acad Sciences, 2026)
Producing multi-layer soundproofing materials by combining materials with different properties is a widely used method. The production of these types of structures utilizes the superior properties of each layer contained within the structure. This study addresses the acoustic performance of nonwoven surface structures fabricated in different thicknesses and densities using chicken feather fibres in different constructions. An impedance tube was used to determine the sound absorption and sound transmission loss values of two-layer structures of different densities and thicknesses. The results show that the influence of the layer in front or behind on the values of sound transmission losses is very limited in two-layer structures with varying densities and thicknesses. However, for the degree of sound absorption, it is important which layer is closer to the sound source. These findings are based on an analysis of multifactorial experimental data. Accordingly, the sound absorption coefficients and sound transmission loss values of all two-layer structures decrease slightly with increasing sound frequency in the frequency range of 63-200 Hz and then increase. The low-density layer on the front of the combined structure ensures better sound absorption at low and medium frequencies. As the density of the front layer increases, its ability to absorb sound decreases. It has been found that the sound absorption capacity of structures with a low density on the front and a thick layer on the back is highest.
Keywords: Chicken feather fibres; acoustic insulation; layered nonwoven surfaces; porous materials; ethylene vinyl acetate polymers; impedance tube